2016
DOI: 10.1152/japplphysiol.00535.2016
|View full text |Cite
|
Sign up to set email alerts
|

Energy substrate utilization with and without exogenous carbohydrate intake in boys and men exercising in the heat

Abstract: Little is known about energy yield during exercise in the heat in boys compared with men. To investigate substrate utilization with and without exogenous carbohydrate (CHO) intake, seven boys [11.2 ± 0.2 (SE) yr] and nine men (24.0 ± 1.1 yr) cycled (4 × 20-min bouts) at a fixed metabolic heat production (Ḣ) per unit body mass (6 W/kg) in a climate chamber (38°C and 50% relative humidity), on two occasions. Participants consumed a C-enriched 8% CHO beverage (CARB) or placebo beverage (CONT) in a double-blinded,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…During long training sessions and matches, some CHO intake may be favourable. Active boys consuming CHO (60 g/L) beverages shifted their relative energy reliance to the exogenous intake in both temperate 289 and hot (38°C) 290 conditions. Sparing endogenous CHO reserves could help delay fatigue and improve performance.…”
Section: Macronutrients Micronutrients and Supplementsmentioning
confidence: 99%
“…During long training sessions and matches, some CHO intake may be favourable. Active boys consuming CHO (60 g/L) beverages shifted their relative energy reliance to the exogenous intake in both temperate 289 and hot (38°C) 290 conditions. Sparing endogenous CHO reserves could help delay fatigue and improve performance.…”
Section: Macronutrients Micronutrients and Supplementsmentioning
confidence: 99%
“…[ 15 , 16 ] reported that prepubertal boys and girls exhibited lower CHO oxidation when compared to same-sex older adolescents while exercising at the same intensity [ 15 , 16 ]. Young boys also exhibited lower total and exogenous CHO oxidation during exercise when compared to adult males [ 13 ]. In a resting state, the pre-pubescent children of the present study had a greater reliance on endogenous CHO oxidation after consuming an exogenous CHO RDC drink.…”
Section: Discussionmentioning
confidence: 99%
“…After consumption of an exogenous carbohydrate (CHO) rich in 13 C, breath tests can be used to monitor the metabolic oxidation of endogenous CHO low in 13 C and the oxidation of the newly introduced exogenous CHO high in 13 C by tracking the 13 C: 12 C isotopic ratios in exhaled CO 2 [ 8 ]. Although breath tests are more commonly used to examine CHO oxidation in adults [ [9] , [10] , [11] , [12] ], this technique has also been applied in children [ [13] , [14] , [15] , [16] ]. For example, Rueda-Maza et al.…”
Section: Introductionmentioning
confidence: 99%
“…An incremental exercise test was performed, using the McMaster All-Out Progressive Continuous Cycling Test. 18,19 The test began at 25 W and had 25-50-W increments every 2 min, according to the participant's height, while maintaining a cadence between 60 and 80 rpm. Measurements of expired VO 2 and VCO 2 were made continuously using calibrated metabolic equipment (Quark CPET, Cardio Pulmonary Exercise Test, COSMED-Italy).…”
Section: Cardiorespiratory Fitnessmentioning
confidence: 99%
“…[208 -(0.7 x age)] = HRmax, 21 (3) respiratory exchange ratio (RER) ≥ 1.0, 22 (4) despite strong verbal encouragement, inability to maintain a cycling cadence above 60 rpm. 18 Heart rate was measured using a heart rate monitor (Polar, S610 USA). Participants should have demonstrated overt signs of extreme physical exertion, such as facial flushing and grimacing, sweating, hyperpnea, and unsteady gait, at the end of the test.…”
Section: Cardiorespiratory Fitnessmentioning
confidence: 99%